Bilateral retinal vasculitis: a presumed case of ocular TB without inflammation. - Umi Kalthum MN,; Norfarizal A,; Rona Asnida N,; Ayesha MZ,; Jemaima CH, (Penerbit UKM, 2012)
A 17-year-old male student of Indonesian parentage presented with two weeks history of progressive painless bilateral visual deterioration. There was no contact with tuberculosis (TB)-infected patients and parents claimed that all immunization including BCG was completed. However, BCG scar was not apparent. Visual acuity was 6/36 and 6/60 in the right and left eyes respectively. The anterior and vitreous chambers were quiet. Funduscopic examination revealed retinal vasculitis with perivascular exudates, branch vein occlusion, neovascularization and macular oedema. Fluorescein angiography confirmed large areas of capillary non-perfusion and leaking new vessels. Mantoux test was positive and full regime anti-TB therapy was instituted. HIV screening was negative. Three days later, an immunosuppressive dose of oral steroid was started. Both eyes received intensive laser photocoagulation. Interestingly, there was no development of vitritis throughout.